Identifikasi Potensi Bahaya dan Analisis Risiko Keselamatan dan Kesehatan Kerja Menggunakan Metode Job Safety Analysis (JSA) pada Tim Dapur Satuan Pelayanan Pemenuhan Gizi (SPPG) X - Naria Juwita; Safrizal Safrizal; Susy Sriwahyuni; Jun Musnadi Is; Fakhrurradhi Luthfi (KOLONI, 2026)
The work environment at the Nutrition Service Unit (SPPG) poses various potential hazards that can affect workers’ safety and health, particularly during food processing and portioning activities. Preliminary observations indicate that workers are at risk of injuries from sharp equipment, heat exposure, and fatigue, as well as inconsistent use of personal protective equipment (PPE). This study aims to identify potential hazards, analyze occupational safety and health risk levels using the Job Safety Analysis (JSA) method, and develop risk control recommendations for the SPPG X kitchen team. The study employed a qualitative method with a descriptive approach. Seven informants were selected through purposive sampling, consisting of the SPPG head, the kitchen manager, the cooking team, and the portioning team. Data collection was conducted through observation, in-depth interviews, and documentation, and was subsequently analyzed using the Miles and Huberman model. The results showed that potential hazards for the cooking team included cuts, burns from hot oil and steam, fire risks from gas stoves, and musculoskeletal disorders resulting from prolonged standing. For the serving team, potential hazards were dominated by ergonomic factors such as static work postures, heavy lifting, and work-related fatigue. The risk assessment indicates that frying and the use of gas stoves fall into the high-risk category, while most other activities fall into the moderate-risk category. Risk control measures must be implemented through the application of SOPs, occupational safety and health (K3) training, consistent use of PPE, ergonomic improvements, routine equipment inspections, and ongoing supervision to create a safer work environment.